ANALISIS UX DAN UI WEBSITE ASPIRASI FRAKSI PKS BERBASIS MODEL KEBERHASILAN SISTEM INFORMASI DELONE & MCLEAN - Hilmiah; Ainayah Al Fathiyyah; Suhardjono Suhardjono (Jurnal Riset Sistem Informasi, 2025)
Ainayah Al Fathiyyah (19210306) Hilmiah (1921030721), UX and UI Analysis of the PKS Faction Aspiration Website Based on the Delone & Mclean Information System Success Model The Aspirasi Information System Website of the Prosperous Justice Party (PKS) is a digital platform designed to facilitate public participation in conveying aspirations directly to legislative representatives. The success of such an information system is not solely determined by its technical functionality but also by its visual quality, ease of user interaction, and perceived security. This study aims to analyze the influence of website quality, features, and security on user satisfaction, using the DeLone and McLean Information System Success Model combined with User Experience (UX) and User Interface (UI) principles.This research applies a quantitative approach through a survey method by distributing questionnaires to respondents who have used the PKS aspiration website. The research instrument is based on a Likert scale and includes several independent variables such as design and interface, features and functionality, and information and accessibility, which are analyzed for their influence on the dependent variable, namely user satisfaction. The data analysis techniques used include validity testing, reliability testing, descriptive statistics, and multiple linear regression analysis. This study is expected to contribute to the evaluation and development of public digital information systems, particularly in the context of political aspiration services that emphasize transparency, participation, and user comfort in online interactions.